A facile one-pot synthesis of FeOx/carbon/graphene composites as superior anode materials for lithium-ion batteries. (1st May 2017) - Han, Cheng-Gong; Zhu, Chunyu; Sheng, Nan; Aoki, Yoshitaka; Habazaki, Hiroki; Akiyama, Tomohiro
Graphical abstract: Highlights: One-pot glycine-nitrate solution combustion synthesis was employed. High performance FeO x /carbon/graphene composite was prepared. The composite showed high discharge capacity 834 mAh g −1 after 100 cycles. The composite displayed high rate capability. Abstract: Iron oxide has been considered as one of the most promising anode materials due to its high theoretical capacity, low cost and environmental friendliness. However, few simple and effective method is explored for preparing iron oxides with high electrochemical performance via alleviating the volume change and agglomeration of active particles. In this work, FeO x /carbon/graphene composites are fabricated by a facile solution combustion synthesis within several minutes in one step. Characterization demonstrates that FeO x nanoparticles are well-dispersed in the graphene matrix. The presence of graphene effectively alleviates the agglomeration of FeO x nanoparticles, and accommodates the volume changes during the cycling process, thereby resulting in the excellent electrochemical performance. FeO x /carbon/graphene (31.4 wt.% graphene) delivers a higher discharge capacity of 824 mAh g −1 after 100 cycles at 0.4 A g −1, in comparison to the value of 301 mAh g −1 for the composite without graphene. This easily prepared FeO x /carbon/graphene composite with excellent electrochemical performance can be considered as one promising anode material used for lithium-ion batteries.